The Impact of Signaling Theory and Human Capital Theory on Self-Branding Strategies Among Gig Workers - Dila Puspa Dara Dinasti; Beny Mahyudi Saputra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This qualitative study aims to explore the self-branding strategies employed by experienced gig workers through the lens of Human Capital Theory and Signaling Theory. Using a multiple case study design, this research analyzes in-depth interviews to understand the life experiences of freelancers navigating a competitive digital marketplace. Thematic analysis reveals a fundamental strategic process. Findings indicate that authentic self-branding is rooted in continuous investment in human capital (substantive expertise), which is then consciously translated into credible market signals (e.g., curated portfolios and client testimonials) to reduce information asymmetry. These elements are further synthesized into a coherent personal brand narrative to communicate unique value. The success of this strategy facilitates the evolution of status from 'freelancer' to 'expert', but is accompanied by the constant burden of reputation management. The main contribution of this study is to demonstrate the interrelated and processual relationship between the two theories in practice, as well as to offer practical insights for workers in the gig economy.